2010
DOI: 10.1371/journal.pone.0009160
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Rabbits with Rabbit and Genotypes 1 and 4 Hepatitis E Viruses

Abstract: BackgroundA recent study provided evidence that farmed rabbits in China harbor a novel hepatitis E virus (HEV) genotype. Although the rabbit HEV isolate had 77–79% nucleotide identity to the mammalian HEV genotypes 1 to 4, their genomic organization is very similar. Since rabbits are used widely experimentally, including as models of infection, we investigated whether they constitute an appropriate animal model for human HEV infection.MethodsForty-two SPF rabbits were divided randomly into eleven groups and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 42 publications
5
79
1
2
Order By: Relevance
“…Infection of SPF rabbits with rabbit HEV induces virus shedding in faeces, viremia and the development of hepatitis, characterised by histopathological changes and an increase in the level of ALT in the serum [95,96,97]. In addition, chronic hepatitis, characterised by liver inflammation and some degree of fibrosis, was observed in rabbits experimentally infected with rabbit HEV [95].…”
Section: Animal Models Of Hevmentioning
confidence: 99%
“…Infection of SPF rabbits with rabbit HEV induces virus shedding in faeces, viremia and the development of hepatitis, characterised by histopathological changes and an increase in the level of ALT in the serum [95,96,97]. In addition, chronic hepatitis, characterised by liver inflammation and some degree of fibrosis, was observed in rabbits experimentally infected with rabbit HEV [95].…”
Section: Animal Models Of Hevmentioning
confidence: 99%
“…Rabbits are susceptible to infection with at least some strains of HEV-3 and HEV-4 but appear to be resistant to infection with HEV-1 (211,212). Conversely, rabbit HEV strains can infect pigs and macaques (213,214), and they can replicate in two human cancer cell lines (96), suggesting the ability to adapt to other mammalian hosts.…”
Section: Scope and Duration Of Protective Immunity To Hev Following Imentioning
confidence: 99%
“…Accumulative lines of evidence have indicated that rabbits are sensitive to HEV infection and seem to constitute an animal reservoir of HEV [34,39]. The fact that rabbits can be experimentally infected by sHEV-4 [40] or human HEV-4 [41] and that rHEV is transmissible from rabbits to cynomolgus macaques [42] both suggest that rabbits may be a new source of human HEV infection. Interestingly, a HEV strain in rabbits closely related to human HEV strain has been identified in France [36], and recently, a HEV strain closely related to a human HEV sequence was identified for the first time in the pet house rabbit [43].…”
Section: Introductionmentioning
confidence: 99%